Immunomodulators and Immunosuppressants for Japanese Patients with Ulcerative Colitis. (25th May 2011) - Bamba, Shigeki; Tsujikawa, Tomoyuki; Sasaki, Masaya; Fujiyama, Yoshihide; Andoh, Akira
Abstract : Ulcerative colitis (UC) is characterized by a long-standing chronic course with remissions and exacerbations. Previously, patients do not respond to 5-aminosalicylic acid compounds and corticosteroids are considered for colectomies, however, in recent years, alternative treatments emerged for steroid-refractory or steroid-dependent UC. In this review article, we focus on immunomodulators (such as azathioprine [AZA] and 6-mercaptopurine [6-MP]) and immunosuppressants (such as cyclosporine A [CSA] and tacrolimus [FK506]) for steroid-refractory or steroid-dependent ulcerative colitis. The characteristics, efficacy and adverse effects of these drugs are outlined. Although the randomized trial of FK506 is conducted in Japan, the clinical data of CSA in Japanese patients are limited. The short-, mid- and long-term follow-ups of CSA administration in Japanese patients are discussed. As for thipurine drugs, the clinical importance of multidrug-resistance protein 4 (MRP4) in Japanese patients is highlighted.